Análise da expressão dos genes TNF, CX3CR1 e TREM2 em um modelo animal de neurodegeneração para a doença de alzheimer - Ibarra, Diany Gisela Arcos (2020)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder and is the leading cause of dementia in late adulthood. Histopathologically, it is characterized by intracellular neurofibrillary tangles and deposits of extracellular amyloid beta protein that contribute to the formation of senile plaques. Several risk factors are associated with AD, triggering neuroinflammation, oxidative stress and cognitive impairment. While the neuropathological features of Alzheimer's disease are recognized, the complexities of the mechanisms associated with its onset and progression have not been clearly elucidated. The aim of the present research was to evaluate the expression of TNF (Tumor Necrosis Factor), CX3CR1 (Chemokine Receptor 1) and TREM2 (Triggering Receptor Expressed on Myeloid cells 2) genes in a model of streptozotocin (STZ) intracerebroventricular (icv) induced neurodegeneration. For this, 20 male Wistar rats were divided into four experimental groups: Group 1 (n = 5, control group 1), composed of animals with icv citrate buffer injection and euthanized 1 month after citrate buffer administration; Group 2 (n = 5), group composed of animals that received STZ via icv, also euthanized after 1 month of neurodegeneration induction; Group 3 (n = 5, control group 2), group that received icv citrate buffer and were euthanized after 4 months of icv administration; Group 4 (n = 5), group that received STZ via icv and were euthanized after 4 months of STZ administration. After euthanasia, the animals had their hippocampus removed for RNA extraction. Total RNA extracted from these samples was converted to cDNA by reverse transcription reaction. Subsequently, the samples will be subjected to quantitative polymerase chain reaction (qPCR) for analyze of TNF, CX3CR1 and TREM2 gene expression. Expression analysis showed increased expression of the TNF gene in animals that were euthanized after 1 month of neurodegeneration induction. Increased expression of the CX3CR1 gene was also found, however, increased expression of this gene was only seen in the group of euthanized animals after 4 months of the icv administration of STZ. These results indicate an association of neuroinflammation with the development and progression of neurodegenerative processes.